Aspek Penegakan Hukum Terhadap Kejahatan Fintech Syariah Pada Masa Pandemi di Indonesia: Perspektif Hukum Jinayah - Ningsih, Sri Wahyu; Fitri, Winda (Universitas Muhammadiyah Sorong, 2022)
With the development of the times, fintech companies in Indonesia are increasingly popular and are also increasingly sought after by many people. One of the developments in fintech is the emergence of Sharia fintech. This study aims to analyze fintech crimes that occur from the perspective of jinayah law and to analyze relevant dispute resolution for fintech crimes from the perspective of jinayah law. In this study, the author uses a normative legal research method that uses qualitative analysis, namely by explaining the existing data with words or statements not with numbers. Sharia fintech has a difference with conventional fintech, namely sharia fintech is carried out in the contract process between business owners and investors. The emergence of sharia fintech provides convenience for the community to carry out a credit process using sharia principles and principles. But there is also a negative side, namely sharia fintech crimes such as fraud, fraud. Based on the results of the study, it shows that this sharia fintech crime when viewed from the perspective of jinayah law is included in the ta'zir crime, which if there is a violation the law enforcement is in accordance with the existing legislation in the fairest manner and carried out indiscriminately and discipline that actually carries out sanki ta'zir for sharia fintech crimes, which in essence contain benefits for human life both in the world and in the hereafter.